A high-conductivity heat-curing HJT solar cell silver paste

By introducing nano-scale fibrous silver powder and high conductive polymer carrier into the silver paste of HJT solar cell, a strong support force and conductive network is formed, which solves the problems of electrode pattern collapse and high resistivity, and improves the conductivity and mechanical reliability of the battery.

CN120356721BActive Publication Date: 2025-08-26XIAN CHUANGLIAN PHOTOVOLTAIC NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510864762.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-08-26
Estimated Expiration
2045-06-26

AI Technical Summary

Technical Problem

The existing HJT solar cell silver paste has a high resistivity after low temperature curing, a large contact resistance with the TCO layer, insufficient electrode resistance and tensile force, and difficult to print, resulting in a degradation of battery performance.

Method used

Nano-scale fibrous silver powder is used to cooperate with silver powder of different structures and high mechanical strength resins to form a conductive network, nano-scale fibrous silver powder is generated through electrospinning and ultraviolet reduction technology, and high-conductive polypyrrole and polythiophene resin are used as organic carriers to form a strong support force and conductive network.

Benefits of technology

The conductivity efficiency of the battery is improved, the electrode pattern is avoided collapse or deformation, the interface adhesion between the electrode and the semiconductor is enhanced, and the filling factor and efficiency of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120356721B_ABST
    Figure CN120356721B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-conductivity, heat-cured HJT solar cell silver paste, which is composed of the following components by weight: 70% to 80% submicron spherical silver powder, 5% to 10% nano-fibrous silver powder, 3% to 6% nano-flake silver powder, 3% to 6% nano-spherical silver powder, and 4% to 9% organic vehicle. The present invention prepares nano-fibrous silver powder through a novel processing method, which improves the efficiency of the conductive network while dispersing the thermal stress generated by the paste during heat curing and enhancing the stability of the conductive layer. At the same time, the use of the same conductive polymer as the organic vehicle has better physical and chemical compatibility with the modified silver powder, reducing the contact resistance of the silver layer while forming a chemical bond with the TCO layer on the surface of the silicon wafer, reducing the contact barrier between the electrode and the semiconductor, improving the short-circuit current and fill factor of the battery, and increasing battery efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of low-temperature HJT solar cell silver paste manufacturing, and in particular relates to a high-conductivity heat-curing HJT solar cell silver paste. Background Art

[0002] HJT (heterojunction cell) was first successfully produced by Sanyo in 1992. By adding a layer of amorphous silicon heterojunction to increase the VOC open circuit voltage, the conversion efficiency of the cell is improved. HJT cells have the advantages of bifacial power generation, high open circuit voltage, no PID phenomenon, high efficiency, high light stability and low-temperature manufacturing process, and have attracted attention from the industry.

[0003] Since HJT cells are currently incompatible with existing equipment, the main difficulties they face are reducing costs and process difficulties. However, their industrialization efficiency is higher than that of TOPCon cells, and they have great potential both in laboratory research and development and in large-scale production. The theoretical limit efficiency of silicon-based heterojunction cells is 28.5%, and the highest efficiency of silicon-based heterojunction cells in the laboratory has reached 26.81%. The main challenges currently encountered in heterojunction pastes are: the low-temperature silver paste is required to have extremely low resistivity after solidification to form an electrode, low contact resistance between the paste and the TCO layer, and good solder resistance and tensile strength of the electrode; the silver paste must reach a viscosity suitable for printing, which can meet the requirements of continuous printing and ensure a good aspect ratio; and the weather resistance requirements of the silver paste after forming the electrode and the weather resistance requirements of the component.

[0004] CN119852004A discloses a low-temperature composite conductive silver paste for HJT solar cells and its preparation method. This invention incorporates silver nanowires into a low-temperature conductive silver paste made from flaky silver powder. The nanowires form a network structure between the flaky silver powder, improving the density and tensile strength of the silver layer. However, excessively long fibrous silver wires can make the paste printing more difficult and more prone to printing defects.

[0005] CN115831439A discloses a low-temperature conductive silver paste suitable for fine grid overprinting for photovoltaic HJT cells and its preparation method. The method comprises: mixing a dispersant, coupling agent, lubricant, and solvent, adding submicron spherical silver powder, and centrifuging to mix uniformly. Subsequently, resin, toughening agent, initiator, latent accelerator, and inhibitor are added and centrifuged to mix uniformly. Finally, micron-sized flaky silver powder, micron-sized spherical silver powder, blocked isocyanate, and modified silicone oil are added and mixed using a three-roll mill to obtain the finished silver paste. This invention improves the fluidity of the silver paste by using a large amount of small-particle silver powder coated with a lipid. This method uses a low-conductivity lipid-coated silver powder, resulting in a high bulk resistivity of the silver layer, which affects the final photoelectric conversion efficiency.

[0006] CN117594285A discloses a self-healing HJT low-temperature silver paste and its preparation method. The paste uses micron-sized spherical silver powder as the primary conductive silver powder and micron-sized flaky silver powder as the secondary conductive silver powder. The self-healing conductive compounds are aniline, pyrrole, thiophene, and their derivatives. While the polymers of aniline, pyrrole, and thiophene used in this invention possess self-healing properties, the cured carrier is relatively soft and has low mechanical strength. The cured silver layer exhibits poor rigidity and wear resistance, resulting in poor weather resistance and shortened battery life. Summary of the Invention

[0007] To address the challenges of the existing technology, the present invention provides a high-conductivity, heat-cured HJT solar cell silver paste. By incorporating in-situ, synchronously generated nanoscale fibrous silver powder, the paste achieves high electrical conductivity while overcoming the problem of conductivity degradation caused by interfacial separation during long-term use. The conductive network formed by the nanoscale fibrous silver powder, combined with the strong support provided by the combination of silver powders with different structures and a high-mechanical-strength resin, improves electrical conductivity while preventing post-printing electrode pattern collapse or deformation, enabling thinner electrode line widths and a high aspect ratio, thereby increasing the cell's fill factor and ultimate efficiency.

[0008] The high-conductivity thermosetting HJT solar cell silver paste provided by the present invention is made of the following raw materials in the following mass percentages: 70% to 80% submicron spherical silver powder, 5% to 10% nanometer fibrous silver powder, 3% to 6% nanometer flaky silver powder, 3% to 6% nanometer spherical silver powder, and 4% to 9% organic carrier.

[0009] Furthermore, the submicron spherical silver powder has a particle size of 400-500 nm and a density of 3.5-4 g / cm 3 The nanoscale silver flakes have a diameter of 1-2 μm, a thickness of 50-100 nm, and a density of 0.91 g / cm 3 The nano-scale spherical silver powder has a particle size of 30 to 50 nm and a density of 0.78 g / cm 3 .

[0010] Furthermore, the nano-scale fibrous silver powder is prepared by the following steps:

[0011] Step 1: Add polyvinyl pyrrolidone and carbon nanotubes to N,N-dimethylformamide and disperse them evenly with ultrasound. Then, add polyvinylidene fluoride under heating and stirring conditions and stir to dissolve. After the solution is cooled and defoamed, silver nitrate and pyrrole monomer are added in sequence and stirred evenly to obtain a spinning solution.

[0012] Step 2: Use a light-proof needle and pipeline to absorb the spinning solution and spin it on an electrospinning machine. At the same time, use an ultraviolet lamp to irradiate the spinning product at the spinning receiving end to reduce silver and polymerize the pyrrole monomer.

[0013] Step 3: The collected spinning products were ultrasonically cleaned in deionized water and then freeze-dried. After drying, they were crushed with a liquid nitrogen grinder and passed through a 400-mesh sieve to obtain nano-scale fibrous silver powder.

[0014] Furthermore, the spinning solution is composed of 75% to 85% N,N-dimethylformamide, 10% to 20% polyvinylidene fluoride, 3% to 6% pyrrole monomer, 0.5% to 3% silver nitrate, 0.5% to 1.5% carbon nanotubes, and 0.1% to 0.5% polyvinyl pyrrolidone by weight.

[0015] Furthermore, the surface area of ​​the carbon nanotubes used is ≥700 m 2 / g, an average diameter of 0.78 nm, and a density of 1.7-1.9 g / cm 3 .

[0016] Furthermore, the spinning solution is transported in a light-proof needle tube and pipeline with a flow rate of 1 to 2 mL / h, a voltage of 15 to 20 kV, a distance between the spinning needle and the collecting device of 15 to 20 cm, a spinning temperature controlled at 25 to 27°C, and a power of the ultraviolet lamp of 5 to 10 W.

[0017] Furthermore, the organic vehicle is made of the following components in percentage by mass: 70-80% curing resin, 10-20% organic solvent, 2-5% curing agent, 1-3% coupling agent, 1-3% dispersant, and 0.5-1% thixotropic agent. The curing resin is any one or more combinations of epoxy resin, polythiophene resin, polypyrrole resin, and acrylic resin; the organic solvent is any one or more combinations of terpineol, butyl carbitol, and phthalate; the curing agent is any one or more combinations of latent imidazole derivative JTN 2025, modified polyamide Aradur 350, and dicyandiamide; the coupling agent is any one or more combinations of KH-550 and KH-560; the dispersant is tributyl citrate or BYK-111; and the thixotropic agent is any one or more combinations of hydrogenated castor oil and polyacrylamide.

[0018] Furthermore, the mass percentage composition of the curing resin is: epoxy resin 40% to 60%, polythiophene resin 10% to 20%, polypyrrole resin 10% to 20%, and acrylic resin 10% to 20%; the mass percentage composition of the organic solvent is: butyl carbitol 50% to 70%, terpineol 10% to 30%, and phthalate 10% to 30%; the mass percentage composition of the curing agent is: latent imidazole derivative JTN 2025 20% to 50%, modified polyamide Aradur 350 20% to 50%, and dicyandiamide 20% to 50%; the mass percentage composition of the coupling agent is: KH-550 30% to 50%, KH-560 50% to 70%; the mass percentage composition of the dispersant is: tributyl citrate 30% to 50%, BYK-111 50% to 70%; the mass percentage composition of the thixotropic agent is: 50% to 80% hydrogenated castor oil and 20% to 50% polyacrylamide.

[0019] The preparation method of the high-conductivity thermosetting HJT solar cell silver paste of the present invention is as follows: according to the mass percentage composition of the silver paste, submicron spherical silver powder, nanometer-level fibrous silver powder, nanometer-level flaky silver powder, and nanometer-level spherical silver powder are first mixed in a mixer for 20 minutes, then transferred to a disperser and an organic carrier is added. The disperser is rotated at a speed of 1000 r / min for every 5 minutes and stopped for 1 minute, and dispersed for a total of 10 minutes to ensure uniform dispersion of the slurry while avoiding high temperature. The slurry is then ground in a three-roll grinder to obtain a finished slurry.

[0020] The beneficial effects of the present invention are as follows:

[0021] 1. The present invention uses polypyrrole with high conductivity as a carrier of nano silver powder, uses a technology combining electrospinning and ultraviolet reduction, reduces silver nitrate while generating highly conductive polypyrrole nanofibers, and directly loads nanoscale silver particles and conductive carbon nanotubes into the polypyrrole to generate a low-cost and highly conductive nanoscale fibrous silver powder. Among them, the polypyrrole with high conductivity and the polyvinylidene fluoride polymer with high mechanical strength are combined to further enhance the interfacial bonding strength with the silver particles, avoiding interface separation during long-term use and causing a decrease in conductivity. At the same time, it can inhibit the oxidation and migration of silver, preventing the problems of increased electrode resistance and battery performance degradation during long-term use.

[0022] 2. The present invention uses the same highly conductive polypyrrole to modify silver powder and organic carriers, which can make the internal components of the slurry system more compatible and the physical and chemical properties more stable. The polymer containing the conjugated π electron system in the polypyrrole can form charge carriers, realize charge transfer through intrachain delocalization or interchain transition, form a continuous conductive path in the silver paste, and cooperate with silver particles of different structures to construct a multidimensional conductive network, reduce the contact gap between silver particles, and reduce the overall resistivity of the slurry. The molecular chain of the conductive polypyrrole forms a chemical bond with the TCO layer on the surface of the silicon wafer through functional groups such as hydroxyl and carboxyl groups, while enhancing the interfacial adhesion, reducing the contact barrier between the electrode and the semiconductor, and improving the short-circuit current and fill factor of the battery. The dispersibility and wettability of polypyrrole can also prevent the agglomeration of silver particles, so that the silver particles are evenly distributed in the slurry, further reducing the consumption of silver.

[0023] 3. During the heat curing process of the silver paste of the present invention, the highly conductive polypyrrole and polythiophene in the organic carrier are matched with the epoxy resin with high mechanical properties to ensure a higher strength skeleton support while having a highly conductive polymer network structure. This prevents the electrode pattern from collapsing or deforming after printing, ensures the accuracy and consistency of the electrode pattern, achieves a finer electrode line width and a high aspect ratio, reduces the electrode shading area, and improves the light receiving efficiency of the battery. The flexibility of polypyrrole and polythiophene can relieve the stress of the electrode during sintering or long-term service, reduce the risk of electrode cracking or falling off, and improve the mechanical reliability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a cross-sectional SEM image of the silver paste after thermal curing in Comparative Example 1.

[0025] Figure 2 This is a cross-sectional SEM image of the silver paste after thermal curing in Example 2.

[0026] Figure 3 This is a cross-sectional SEM image of the silver paste after thermal curing in Comparative Example 3.

[0027] Figure 4 This is a cross-sectional SEM image of the silver paste after thermal curing in Example 3. DETAILED DESCRIPTION

[0028] The technical solutions of the present invention are described clearly and completely below with reference to the accompanying drawings and embodiments. It is apparent that the embodiments described are only a portion of the embodiments of the present invention, not all of them. All other embodiments derived by those skilled in the art based on the embodiments of the present invention without creative effort are intended to fall within the scope of protection of the present invention. Example 1

[0029] The high-conductivity thermosetting HJT solar cell silver paste of this embodiment is made of the following raw materials in the following mass percentages: 80% submicron spherical silver powder, 5% nano-fibrous silver powder, 4% nano-flake silver powder, 4% nano-spherical silver powder, and 7% organic vehicle.

[0030] The submicron spherical silver powder used in this embodiment has a particle size of 400-500 nm and a density of 3.5-4 g / cm 3 The nanoscale flaky silver powder has a diameter of 1-2 μm, a thickness of 50-100 nm, and a density of 0.91 g / cm 3 The nano-scale spherical silver powder has a particle size of 30 to 50 nm and a density of 0.78 g / cm 3 .

[0031] The nano-fibrous silver powder used in this embodiment was prepared by the following steps:

[0032] Step 1: Mix 0.2 g polyvinyl pyrrolidone and 1 g carbon nanotubes (surface area ≥ 700 m 2 / g, an average diameter of 0.78 nm, and a density of 1.7-1.9 g / cm 3 ) was added to 79.8 g of N,N-dimethylformamide and ultrasonically dispersed. Then, 10 g of polyvinylidene fluoride was added under heating at 60°C in a water bath and stirred to dissolve. After the solution was cooled and defoamed, 3 g of silver nitrate and 6 g of pyrrole monomer were added in sequence and stirred evenly to obtain a spinning solution.

[0033] Step 2: Use a light-proof needle and pipeline to absorb the spinning solution and spin it on an electrospinning machine. The spinning solution flow rate is 12 mL / h, the voltage is 20 kV, the distance between the spinning needle and the collecting device is 15 cm, and the spinning temperature is controlled at 25°C. At the same time, a 10 W ultraviolet lamp is used at the spinning receiving end to irradiate the spinning product to reduce silver and polymerize the pyrrole monomer.

[0034] Step 3: The collected spinning products were ultrasonically cleaned in deionized water and then freeze-dried. After drying, they were crushed with a liquid nitrogen grinder and passed through a 400-mesh sieve to obtain nano-scale fibrous silver powder.

[0035] The organic vehicle used in this example is made of the following components by weight: 80.5% curing resin, 15% organic solvent, 2% curing agent, 1% coupling agent, 1% dispersant, and 0.5% thixotropic agent. The curing resin comprises 50% epoxy resin, 20% polythiophene resin, 20% polypyrrole resin, and 10% acrylic resin; the organic solvent comprises 70% butyl carbitol, 10% terpineol, and 20% phthalate; the curing agent comprises 30% latent imidazole derivative JTN 2025, 30% modified polyamide Aradur 350, and 40% dicyandiamide; the coupling agent comprises 50% KH-550 and 50% KH-560; the dispersant comprises 40% tributyl citrate and 60% BYK111; and the thixotropic agent comprises 60% hydrogenated castor oil and 40% polyacrylamide. The above substances were weighed in a stainless steel barrel and dispersed using a disperser with the machine stopped every 20 minutes to allow the heat to cool to room temperature. The total dispersion time was 2 hours to obtain an organic carrier.

[0036] The preparation method of the high-conductivity thermosetting HJT solar cell silver paste in this embodiment is as follows: submicron spherical silver powder, nanometer-level fibrous silver powder, nanometer-level flaky silver powder, and nanometer-level spherical silver powder are mixed in a mixer for 20 minutes, then transferred to a disperser and an organic carrier is added. The disperser is rotated at a speed of 1000 r / min for every 5 minutes and stopped for 1 minute, and the total dispersion time is 10 minutes to ensure uniform dispersion of the slurry while avoiding high temperature. The slurry is then ground in a three-roll grinder to obtain a finished slurry. Example 2

[0037] The high-conductivity thermosetting HJT solar cell silver paste of this embodiment is made of the following raw materials in percentage by mass: 78% submicron spherical silver powder, 7% nano-fibrous silver powder, 4% nano-flake silver powder, 4% nano-spherical silver powder, and 7% organic vehicle.

[0038] The properties and preparation methods of the raw materials used in this embodiment are the same as those in Example 1, and the preparation method of the silver paste is also the same as that in Example 1. Example 3

[0039] The high-conductivity thermosetting HJT solar cell silver paste of this embodiment is made of the following raw materials in the following mass percentages: 76% submicron spherical silver powder, 9% nano-fibrous silver powder, 4% nano-flake silver powder, 4% nano-spherical silver powder, and 7% organic vehicle.

[0040] The properties and preparation methods of the raw materials used in this embodiment are the same as those in Example 1, and the preparation method of the silver paste is also the same as that in Example 1. Comparative Example 1

[0041] The HJT solar cell silver paste of this comparative example is made of the following raw materials in percentage by mass: 85% of submicron spherical silver powder, 4% of nano-scale flaky silver powder, 4% of nano-scale spherical silver powder, and 7% of organic vehicle.

[0042] The properties and preparation methods of the raw materials used in this comparative example are the same as those in Example 1, and the preparation method of the silver paste is also the same as that in Example 1. Comparative Example 2

[0043] The HJT solar cell silver paste of this comparative example is made of the following raw materials in percentage by mass: 78% submicron spherical silver powder, 7% nano-fibrous silver powder, 4% nano-flake silver powder, 4% nano-spherical silver powder, and 7% organic vehicle;

[0044] In the preparation method of the nano-fibrous silver powder used in this comparative example, 0.2 g of polyvinylpyrrolidone was added to 79.8 g of N,N-dimethylformamide and ultrasonically dispersed. Then, 10 g of polyvinylidene fluoride was added under heating in a water bath at 60°C and stirred to dissolve. After the solution was cooled and defoamed, 3 g of silver nitrate and 7 g of pyrrole monomer were added in sequence and stirred uniformly to obtain a spinning solution. The other steps were the same as the preparation method of the nano-fibrous silver powder in Example 1.

[0045] The properties and preparation methods of other raw materials used in this comparative example are the same as those in Example 1, and the preparation method of the silver paste is also the same as that in Example 1. Comparative Example 3

[0046] In the HJT solar cell silver paste of this comparative example, the mass percentage composition of the curing resin is: 50% epoxy resin and 50% acrylic resin. Other raw materials and their preparation methods are the same as those in Example 1.

[0047] The silver pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were printed using HJT silicon wafers of the same specifications, the same screens, and printing parameters, and cured at 200°C for 20 minutes, and then subjected to relevant performance tests. The viscosity was tested using an NDJ-8S viscometer at 20-25°C, rotor No. 5, and a rotation speed of 10 r / min. The thixotropy was tested using a rheometer to simulate the viscosity changes of the silver paste after high shear and shear force removal during printing. The viscosity recovery of the paste 1 minute after the shear force was removed was tested. The higher the viscosity recovery ratio, the better the thixotropy. The aspect ratio was measured using a microscope. The adhesion was tested using 3M#600 tape. The volume resistivity was tested using a four-probe method. The performance of the solar cell was tested on a solar integrated measurement system. The test results are shown in Tables 1 and 2.

[0048] Table 1

[0049]

[0050] It can be seen from the data in Table 1 that as the proportion of nano-fibrous silver powder added to the silver paste increases, the viscosity of the paste tends to rise. This is because the fluidity of nano-fibrous silver powder is lower than that of spherical silver powder and flaky silver powder. However, the combination of silver powders with different structures can increase the thixotropy of the paste, and the paste has a higher aspect ratio than that of Comparative Example 1. As the proportion of nano-fibrous silver powder added to the silver paste increases, the one-dimensional composite silver powder has a good mechanical structure and thermal dispersion ability during the thermosetting reaction, so that the cured silver layer has better adhesion and avoids the problem of uneven stress distribution of the silver layer caused by the explosion of the polymer in the organic carrier. The lack of conductive carbon nanotubes in Comparative Example 2 and the increase in the content of epoxy resin and acrylic resin in the organic carrier in Comparative Example 3 increase the viscosity of the paste. Although the tensile force is improved, it also leads to poor printability and dispersibility.

[0051] Table 2 Photovoltaic cell performance comparison data

[0052]

[0053] As shown in Table 2, as the proportion of nano-fibrous silver powder added to the silver paste increases, its various electrical properties are improved. As shown in the data of Example 2 and Comparative Example 3, the absence of carbon nanotubes increases the resistance between the silver powder particles and reduces the various electrical properties. As shown in the data of Example 2 and Comparative Example 3, the polypyrrole and polythiophene highly conductive polymers in the organic carrier interact with the main chain of the epoxy resin, which can well maintain the printed shape and suppress line expansion and collapse. At the same time, the conductive polymer forms an interface dipole on the surface of the silver, which increases FF.

[0054] exist Figure 1 In Comparative Example 1, the silver powder distribution after the silver paste is solidified is not very dense, and many black voids of 2 to 3 μm are dispersed therein. Figure 2 In Example 2, after the silver paste is thermally cured, the silver powder with different structures and the polymer with high mechanical properties are matched with each other to enhance the support capacity of the printing layer, achieve a finer electrode line width and a high aspect ratio, ensure the accuracy and consistency of the electrode pattern, and avoid Figure 1 The problem of electrode pattern collapse or deformation after printing. Figure 4 In Example 3, the uniformity and density of the silver layer after the silver paste is thermally cured are compared with Figure 3 Comparative Example 3 is superior. After printing and curing, the uniformly distributed and dense silver layer in Example 3 effectively transfers charge and provides more complete contact with the substrate, resulting in improved conductivity and tensile strength. These results demonstrate that the present invention, by adding nano-fibrous silver powder and combining it with a highly conductive organic carrier, can effectively enhance the various properties of HJT low-temperature silver paste.

Claims

1. A high-conductivity heat-curing HJT solar cell silver paste, characterized by: The silver paste is made of the following raw materials in percentage by mass: 70% to 80% submicron spherical silver powder, 5% to 10% nano-fibrous silver powder, 3% to 6% nano-flake silver powder, 3% to 6% nano-spherical silver powder, and 4% to 9% organic carrier; The nano-scale fibrous silver powder is prepared by the following steps: Step 1: adding polyvinyl pyrrolidone and carbon nanotubes to N,N-dimethylformamide, ultrasonically dispersing them uniformly, then adding polyvinylidene fluoride under heating and stirring conditions, stirring to dissolve, and after the solution is cooled and defoamed, adding silver nitrate and pyrrole monomer in sequence and stirring uniformly to obtain a spinning solution; the spinning solution has a mass percentage composition of: N,N-dimethylformamide 75% to 85%, polyvinylidene fluoride 10% to 20%, pyrrole monomer 3% to 6%, silver nitrate 0.5% to 3%, carbon nanotubes 0.5% to 1.5%, and polyvinyl pyrrolidone 0.1% to 0.5%; Step 2: Using a light-proof needle and pipeline to absorb the spinning solution, spinning is carried out on an electrospinning machine, and the spinning product is irradiated with an ultraviolet lamp. The spinning solution is transported in the light-proof needle and pipeline at a flow rate of 1 to 2 mL / h, a voltage of 15 to 20 kV, a distance between the spinning needle and the collecting device of 15 to 20 cm, a spinning temperature controlled at 25 to 28°C, and a power of the ultraviolet lamp of 5 to 10 W. Step 3: The collected spinning product was ultrasonically cleaned in deionized water and then freeze-dried. After drying, it was crushed with a liquid nitrogen crusher and passed through a 400-mesh sieve to obtain nano-scale fibrous silver powder; The organic carrier is composed of a curing resin, an organic solvent, a curing agent, a coupling agent, a dispersant, and a thixotropic agent, wherein the mass percentage of the curing resin is: 40% to 60% epoxy resin, 10% to 20% polythiophene resin, 10% to 20% polypyrrole resin, and 10% to 20% acrylic resin.

2. The high-conductivity heat-curing HJT solar cell silver paste according to claim 1, wherein: The submicron spherical silver powder has a particle size of 400-500 nm and a density of 3.5-4 g / cm 3 The nano-scale flaky silver powder has a flake diameter of 1-2 μm, a thickness of 50-100 nm, and a density of 0.91 g / cm³; the nano-scale spherical silver powder has a particle size of 30-50 nm and a density of 0.78 g / cm³. 3 .

3. The high-conductivity heat-curing HJT solar cell silver paste according to claim 1, wherein: The surface area of ​​the carbon nanotubes is ≥700 m 2 / g, diameter is 0.5-1 nm, density is 1.7-1.9 g / cm 3 .

4. The high-conductivity heat-curing HJT solar cell silver paste according to claim 1, wherein: The organic vehicle is made of the following components in percentage by mass: 70-80% curing resin, 10-20% organic solvent, 2-5% curing agent, 1-3% coupling agent, 1-3% dispersant, and 0.5-1% thixotropic agent; wherein the organic solvent is any one or more combinations of terpineol, butyl carbitol, and phthalate; the curing agent is any one or more combinations of latent imidazole derivative JTN 2025, modified polyamide Aradur 350, and dicyandiamide; the coupling agent is any one or a combination of two of KH-550 and KH-560; the dispersant is any one or a combination of two of tributyl citrate and BYK-111; and the thixotropic agent is any one or a combination of two of hydrogenated castor oil and polyacrylamide.

5. The high-conductivity heat-curing HJT solar cell silver paste according to claim 4, wherein: The mass percentage composition of the organic solvent is: 50% to 70% butyl carbitol, 10% to 30% terpineol, and 10% to 30% phthalate; the mass percentage composition of the curing agent is: 20% to 50% latent imidazole derivative JTN 2025, 20% to 50% modified polyamide Aradur 350, and 20% to 50% dicyandiamide; the mass percentage composition of the coupling agent is: 30% to 50% KH-550 and 50% to 70% KH-560; the mass percentage composition of the dispersant is: 30% to 50% tributyl citrate and 50% to 70% BYK111; the mass percentage composition of the thixotropic agent is: 50% to 80% hydrogenated castor oil and 20% to 50% polyacrylamide.

Citation Information

Patent Citations

  • HJT low-temperature silver paste with self-healing function and preparation method thereof

    CN117594285A

  • Low-temperature curing conductive silver paste for solar HJT fine grid and preparation method of low-temperature curing conductive silver paste

    CN113707365A

  • Low-temperature composite conductive silver paste for HJT solar cell and preparation method of low-temperature composite conductive silver paste

    CN119852004A